Experimental and Theoretical Validation of Room Temperature Intrinsic Ferromagnetism in Cr3C2 Due to Interstitial Carbon Atoms. Issue 11 (18th August 2022) - Javid, Muhammad; Jiang, Xue; Gao, Yinlu; Zhao, Lizhong; Zhang, Xuefeng; Xu, Xiaohui; Farid, Amjad; Saleem, Muhammad Farooq; Zuo, Xueqing; Zhao, Yongpeng; Pan, Lujun; Dong, Xinglong
Abstract : Ferromagnetism is explored in Cr3 C2 from microscopic to electronic levels and the spin coupling is attributed to the p electrons of the nearest‐neighbor carbon atoms around the Cr–C atomic interactions. By using the spin‐polarized density functional calculations, four models are formulated. The models reveal that the C atoms seated in tri‐prism I site can induce magnetic moments and the C vacancies can also take part in the induced magnetic moment. The p – d orbital interactions between C interstitial atom and Cr atom contribute to two asymmetric states of majority and minority spins and lead to weak magnetic moments. The C interstitial atoms and C vacancies in the crystal lattice of Cr3 C2 are observed by high‐resolution transmission electron microscopy and electron‐spin resonance (ESR) techniques. The magnetic properties of Cr3 C2 are investigated by a superconducting quantum interference device. Abstract : Ferromagnetism is explored from microscopic to electronic levels in Cr3 C2 nanocapsules (NCs). Our density functional theory calculations reveal that the carbon atoms seated in C‐triprs I sites along with C atoms vacancies can induce magnetic moments. Magnetic signal in Cr3 C2 NCs experimentally recognizes through electron‐spin resonance (ESR) and superconducting quantum interference device techniques.